The Role of the History of Islamic Education in Improving Morals in Adolescents - Muhammad Sapii Harahap (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this research is to find out what causes delinquency in children, and how to deal with delinquency in these children. This research uses literature research (library research) or library research with a qualitative approach. This type of research is research where the research data comes from books, journals, books and other scientific writings. In collecting data, documentation techniques were used. The data sources collected in this research consist of primary and secondary data sources. The primary data from this research are several verses from the Koran, hadiths of the Prophet and books of interpretation. The secondary data in this research is in the form of documents that support this research such as books, articles and journals. The conclusions from this research are: 1) The biggest factors that make children naughty and deviant are: a) Poverty that the family suffers from, b) Disputes and quarrels between father and mother, c) Divorce accompanied by poverty, d) Leisure that takes up time children and teenagers, e) Mother's busyness when the child is 0-13 years old, f) Bad environment and friends, and g) Parents' negligence regarding children's education. 2) The solution to dealing with child delinquency from the historical perspective of Islamic education is: a) Meeting Family Needs, b) Harmony between Father and Mother, c) Forgive each other and help each other, d) Keep yourself busy with your children, e) A mother focuses on accompanying her child at least until the age of 12 years, f) Good Environment and Friends, and g) Parents must focus on their children's education.